New LMI-Based Conditions on Neural Networks of Neutral Type with Discrete Interval Delays and General Activation Functions. (8th November 2012) - Liu, Guoquan; Zhou, Shumin; Huang, He
Abstract : The stability analysis of global asymptotic stability of neural networks of neutral type with both discrete interval delays and general activation functions is discussed. New delay-dependent conditions are obtained by using more general Lyapunov-Krasovskii functionals. Meanwhile, these conditions are expressed in terms of a linear matrix inequality (LMI) and can be verified using the MATLAB LMI toolbox. Numerical examples are used to illustrate the effectiveness of the proposed approach.